Notation publications in the context of musical life in Lithuania in the XVI-XVII centuries - Jūratė Trilupaitienė (Knygotyra)
In the 16th and 17th centuries, musical notation was only a modest part of the published output in Lithuania. What was new in the large centers of music in Western Europe spread here and was incorporated into this country's musical life, but due to specific political and cultural factors, this did not ensure an even musical development. Lithuania had no long-standing tradition of sponsorship by patrons of the arts, and the publication of notated music was limited to religious purposes and thus highlighted the main musical accents in Lithuanian church music.